2014
DOI: 10.12988/ces.2014.48116
|View full text |Cite
|
Sign up to set email alerts
|

Study generator of a cold plasma for sterilization

Abstract: An effective method of sterilization and disinfection of various surfaces using cold plasma is presented in this work. The results of interaction of the cold-plasma with the test objects are presented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…To conduct experimental studies, the cold plasma generator was developed, shown in Figure 1 [6][7][8][9][10]. Seeds of various crops, including wheat and barley, were exposed to the cold plasma.…”
Section: Experimental Studiesmentioning
confidence: 99%
“…To conduct experimental studies, the cold plasma generator was developed, shown in Figure 1 [6][7][8][9][10]. Seeds of various crops, including wheat and barley, were exposed to the cold plasma.…”
Section: Experimental Studiesmentioning
confidence: 99%